2010
DOI: 10.1039/c0sc00107d
|View full text |Cite
|
Sign up to set email alerts
|

Diamine ligands in copper-catalyzed reactions

Abstract: The utility of copper-mediated cross-coupling reactions has been significantly increased by the development of mild reaction conditions and the ability to employ catalytic amounts of copper. The use of diamine-based ligands has been important in these advances and in this review we discuss these systems, including the choice of reaction conditions and applications in the synthesis of pharmaceuticals, natural products and designed materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
208
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(215 citation statements)
references
References 225 publications
(365 reference statements)
3
208
0
4
Order By: Relevance
“…20% (14)(15)(16)(17). The use of 2,6-dimethylphenol, hindered at both sides, considerably reduces the reactivity, and coupling products with 4-iodoanisole and 2-iodotoluene were obtained in 37% and 22% yield respectively (18)(19). The coupling of 3,5-dimethylphenol with 2-iodotoluene furnished 20 in 45% yield, but the reaction with 4-iodoaniline or 2-iodoaniline afforded 79% and 71% yield respectively (21)(22).…”
Section: Arylation Of Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…20% (14)(15)(16)(17). The use of 2,6-dimethylphenol, hindered at both sides, considerably reduces the reactivity, and coupling products with 4-iodoanisole and 2-iodotoluene were obtained in 37% and 22% yield respectively (18)(19). The coupling of 3,5-dimethylphenol with 2-iodotoluene furnished 20 in 45% yield, but the reaction with 4-iodoaniline or 2-iodoaniline afforded 79% and 71% yield respectively (21)(22).…”
Section: Arylation Of Phenolsmentioning
confidence: 99%
“…15,16 Copper-catalysed coupling reactions have recently attracted much attention, even at an industrial level, due to the lower toxicity and cost than heavier transition metal catalysts, and considerable research has been undertaken regarding ligands, scope and mechanism. [17][18][19][20] Green media have been investigated for their use in copper-catalysed arylations since the late 2000s, and now many examples of reactions performed in aqueous solvents can be found in the literature. 17,21 Water is frequently used as a co-solvent for these processes in mixtures with DMSO or DMF.…”
Section: Introductionmentioning
confidence: 99%
“…Since vicinal diamines constitute an important class of functional groups that are present in a number of molecular entities of pharmaceutical and medicinal interest, 7 function as effective ligands to transition metals to provide catalysts, 8,9 the development of new avenues for their synthesis is of major interest. Within this context, the direct vicinal diamination of alkenes offers a straightforward access, 10 and we have been interested in devising suitable reaction conditions that enable palladium catalysis to operate under completely intermolecular conditions.…”
mentioning
confidence: 99%
“…Since Miura and co-workers reported that CuI/PPh 3 catalyzed cross-couplings of aryl iodides and terminal alkynes, [13] much attention has been focused on the use of copper complexes as the catalysts for the Sonogashira cross-coupling for copper is less toxic and far more economic than palladium. [14][15][16][17][18][19][20][21] Although copper-based catalysts have been proposed as an alternative to palladium-based catalysts for Sonogashira couplings, these catalyst systems generally require high copper loadings to maintain a catalytic cycle. Therefore, the development of an efficient reaction system with recyclable copper catalysts is highly desirable.…”
Section: Introductionmentioning
confidence: 99%